(untitled) (The Journal of Psychology and Sociology, 2017)
The article raises the problem of relation to the punishment of criminal person with a different type of violent criminal experience. Changes that have occurred in the modern Kazakh society in the spheres of economic and political life of the country are reflected in the penal system. Concerning the study the problem of penal is actual, as happened changes entailed changes in social features of the person identity the modern criminal. Moreover, the natures of these changes are so significant that allows criminals to notice significant differences of the past and the present. Convicted - recidivists exhibit denial of punishment perceive it, bans, the process of obtaining a new criminal experience but not method of correction. They do not see the meaning in punishment, they don’t have future prospective, and as a result, there is no awareness of his guilt. Thus, the perception of the punishment depends on the level of criminal experience. The criminal experience of the inmates leads to, the negative attitude to punishment